An immunosufficient murine model for the study of human islets. (9th July 2014) - Zhao, Gaoping; Moore, Daniel J.; Kim, James I.; Lee, Kang Mi; O'Connor, Matthew; Yang, Maozhu; Marshall, Andrew F.; Lei, Ji; Schuetz, Christian; Markmann, James F.; Deng, Shaoping
Abstract For the sake of therapy of diabetes, it is critical to understand human beta cell function in detail in health and disease. Current studies of human beta cell physiology in vivo are mostly limited to immunodeficient mouse models, which possess significant technical limitations. This study aimed to create a new model for the study of human islets through induction of transplant tolerance in immunosufficient mice. B6 diabetic mice were transplanted with human islets and treated with anti‐CD45RB. To assess whether anti‐CD45RB‐induced transplant tolerance requires B cells, B6 recipients received additional anti‐CD20 or B6μMT−/− mice were used. For some anti‐CD45RB‐treated B6μMT−/− mice, additional anti‐CD25 mAb was applied at the early or late stage post‐transplant. Immunohistology was performed to show the Foxp3 cells in grafted anti‐CD45RB/anti‐CD20‐treated Foxp3‐GFP B6 mice. The results showed that anti‐CD45RB alone allowed indefinite graft survival in 26.6% of B6 mice, however 100% of xenografts were accepted in mice treated simultaneously with anti‐CD20, and 88.9% of xenografts accepted in anti‐CD45RB‐treated μMT−/− mice. These μMT−/− mice accepted the islets from another human donor but rejected the islets from baboon. Additional administration of anti‐CD25 mAb at the time of transplantation resulted in 100% rejection, whereas 40% of grafts were rejected while the antibody was administrated at days 60 post‐transplant. Immunohistologic examination showed Foxp3+ cells accumulated around grafts. We conclude that induction of tolerance to human islets in an immunosufficient mouse model could be generated by targeting murine CD45RB and CD20. This new system will facilitate study of human islets and accelerate the dissection of the critical mechanisms underlying islet health in human disease.